PENGARUH RENDAM KAKI DENGAN AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI: SCOPING REVIEW - Dewi, Ni Komang Mia Sintya; Dwijayanto, I Made Rio; Kusumaningtiyas, Dwi Prima Hanis (Universitas Prima Indonesia, 2023)
Elderly or often called the elderly is an age group that is prone to health problems. The more a person gets older the experienced will cause all systems and functions to decrease. One function that has decreased is physiological function. This decrease in physiological function gives rise to non-communicable and communicable diseases. Some of the non-communicable diseases experienced by the elderly are hypertension, arthritis, stroke, and diabetes mellitus. Hypertension ranks first in health problems for the elderly. Hypertension or high blood pressure is when a person experiences an increase in blood pressure which is characterized by a systolic number of more than 140 mmHg and a diastolic number of more than 90 mmHg. Several treatments for lowering blood pressure can be carried out with pharmacological and non-pharmacological actions. This study aims to determine the benefits of soaking feet in warm water which can be used as a non-pharmacological treatment to reduce blood pressure. The literature review uses secondary data taken from Google Scholar. The results of this literature review present articles regarding the benefits of soaking feet in warm water to reduce blood pressure in elderly hypertensives.